The lithium investment in Portugal: Potential benefits and challenges - Bastos, Diogo Alexandre Pereira (2023)
The pivot towards a cleaner, more sustainable future places lithium, a quintessential component for energy storage and electric mobility, firmly in the global spotlight. Portugal, harboring substantial lithium reserves, stands at a confluence where economic development and sustainable practices are intricately entwined, necessitating a rigorous exploration of the avenues and challenges birthed by lithium exploration endeavors. This thesis seeks to navigate through the complex tableau of potential economic benefits, juxtaposed against the myriad challenges dispersed across environmental, social, and regulatory spheres. The research is distilled into poignant research questions aimed at dissecting the economic impacts and confronting the feasibility and sustainability of lithium projects in the nation, underpinned by an empirically-informed analysis through an examination of relevant secondary data. Woven into the fabric of the study are critical aspects including the literature review, contextual exploration of lithium in Portugal and comprehensive discussions on findings and recommendations. Although the research dances within certain limitations, primarily tethered to the utilization of secondary data and the geographical and methodological confines, it aspires to emerge as a significant academic and practical contribution, illuminating pathways for policy-making, industry strategies, and further research.